THE ENGLISH VOCABULARY SIZE AND LEVEL OF ENGLISH DEPARTMENT STUDENTS AT KUTAI KARTANEGARA UNIVERSITY - Sudarman Sudarman; Sumalee Chinokul (Universitas Islam Negeri Alauddin Makassar, 2018)
The study employed descriptive-quantitative research design which aimed to investigate the mean vocabulary size and mastery level of English department students. The subjects of the study were the first-year students majoring in English education department at Kutai Kartanegara University. Thirty-three students employed in this study were given the Vocabulary Levels Test (VLT) to measure their English vocabulary size as well as their mastery level. The findings of this study revealed that the students only knew about 1,273 word families. The result was still below the threshold as suggested by the vocabulary scholars and was not improved after years of learning. The finding also showed that the participants had a very low mastery level. They did not even master the 2,000 or 3,000 high frequency word level, nor the academic vocabulary level. The results indicate that the participants had a low vocabulary proficiency and suggest the future research to focus on investigating the vocabulary learning and instruction strategies that are effective to develop the students’ high frequency words and academic words.